INTEGRATED BIOSTRATIGRAPHY OF EOCENE DEPOSITS IN THE GUBS SECTION (NORTHERN CAUCASUS) WITH SPECIAL ATTENTION TO THE YPRESIAN/LUTETIAN BOUNDARY AND TO THE PERITETHYAN-TETHYAN CORRELATION - Zakrevskaya, E.; Beniamovsky, V.; Less, G.; Baldi-Beke, M. (My University, 2011)
Th e Ypresian to Priabonian Gubs river section, in the Adygean high of the northern slope of the Caucasus, is a rare locality, in whichYpresian–Lutetian representative larger benthic foraminifera coexist with planktonic Foraminifera and calcareous nannoplankton. Th is provides a good opportunity to apply and refi ne the zonal Ypresian–Lutetian scheme of the Crimean-Caucasus region, to correlate the zonal subdivision of the three most important Palaeogene groups of microfossils and to give a new insight on the position of the Ypresian/Lutetian boundary. About 50 species and subspecies of larger foraminifera, represented by orthophragmines (Discocyclina, Nemkovella, Orbitoclypeus and Asterocyclina) and nummulitids (Nummulites and Operculina) are identifi ed and one new species (Orbitoclypeus barkhatovae) is introduced. Based mainly on phylogenetic successions of orthophragmines (mostly Orbitoclypeus and also Discocyclina) the section is correlated with the SBZ 11-15 zones of the Tethyan shallow benthic scale and with the OZ 7-11 zones of the orthophragminid scale. Th e planktonic foraminiferal zonal subdivision of the Gubs Eocene is based on the infrazonal detailed regional Crimean-Caucasus scale whose PF 10a to 13b, 14a and 16 zones/subzones corresponding to the P 7 to 12 and 15 zones of the standard scale could be recognized. Th e calcareous nannoplankton allowed establishment of the NP 12 to 19–20 zones. Our results are mostly in accord with those from the Southern Pyrenees, where the GSSP of the Ypresian/Lutetian boundary was recently fi xed in the Gorrondatxe section at the boundary of the NP 14a/b calcareous nannoplankton subzones defi ned by the fi rst appearance of Blackites infl atus. Th is boundary corresponds in the Gubs section to about the base of the SBZ 12 larger foraminiferal zone, having formerly indicated the base of the late Cuisian. In terms of planktonic foraminifera it falls within the Acarinina bullbooki (PF 11) Zone, formerly placed into the early Lutetian in the Crimean-Caucasus regional scale. Th e appearance of warm-water Hantkenina may refl ect palaeogeographic conditions (hydrology, deepness, currents) for particular areas and cannot be applied as a marker for the Ypresian/Lutetian boundary.
Keywords: North-Western Caucasus; Ypresian–Lutetian; orthophragmines; nummulitids; planktonic foraminifera; nannoplankton; correlation; Cenozoic::Paleogene::Eocene::Lutetian; Cenozoic::Paleogene::Eocene::Ypresian; Кайнозой::Палеоген::Эоцен::Ипрский